High frequency modulation and injection locking of terahertz quantum cascade lasers. (25th May 2017) - Gu, L; Wan, W J; Zhu, Y H; Fu, Z L; Li, H; Cao, J C
Abstract: Due to intersubband transitions, the quantum cascade laser (QCL) is free of relaxations and able to work under fast modulations. In this work, the authors investigate the fast modulation properties of a continuous wave (cw) terahertz QCL emitting around 3 THz (∼100 μ m). Both simulation and experimental results show that the 3 dB modulation bandwidth for the device can reach 11.5 GHz and the modulation response curve is relatively flat upto ∼16 GHz. The radio frequency (RF) injection measurements verify that around the laser threshold the inter-mode beat note interacts strongly with the RF signal and the laser can be modulated at the round trip frequency of 15.5 GHz.